Fun and fear in False Bay Nature Reserve: green space affordances in the post-apartheid city - Baigrie, Bruce (Percy FitzPatrick Institute of African Ornithology, 2015)
The phenomenon and increasing rate of urbanisation is causing many researchers to look deeper at life in cities. Increasingly recognised are the benefits of urban green space and their associated recreational parks and nature reserves. While there is a growing literature on the environmental services provided by these areas; so too is there a growing literature on the numerous social benefits that recreational green spaces in particular afford their users. Although imagined and generally designed as salubrious public spaces, many parks often fall short of this. In fact research has shown that a park's design, its surroundings, and its management can all combine to exclude certain types of people. In this study I conducted ethnographic research to participate in and observe the activities of visitors to False Bay Nature Reserve in Cape Town. False Bay Nature Reserve includes a series of nature reserves and the Cape Flats Waste Water Treatment Works, and is situated in the area of Cape Town known as the Cape Flats. Much of the Cape Flats is beset by poverty, unemployment, and violent drug - related crime carried out by notorious gangs. Despite the challenges of the surrounding areas, my study reveals that False Bay Nature Reserve provides relative safety to its users as well a range of enjoyable re creational activities. Some of the key recreational activities are separated distinctively between two key sites in the reserve. Furthermore the visitors of these sites differ markedly in race, ethnicity and income. The legacy of apartheid almost certainly accounts for much of this separation; however, the study indicates that the barriers of this legacy are eroding and can potentially be further dismantled with engaged and informed management strategies. Due to its surroundings, the reserve is vulnerable and recently experienced a period where crime was prevalent, vegetation was overgrown, and it was feared by many of its users, particularly women. The reserve had in many ways become what researchers call a landscape of fear, a not so uncommon description of parks around the world. However, management and the majority of visitors feel the reserve has recovered from this period. This is in large part due to upgrades that improved recreational facilities and security in the reserve. Accounts from visitors high light how important a sense of safety is for people frequenting this reserve, most of who live in nearby neighbourhoods. The reserve still faces some challenges today, but is a significant asset to the City of Cape Town and many of its more marginalised residents. This study challenges much of the literature on the benefits of urban green space and associated parks. It shows that particularly in cities of the Global South such as Cape Town, parks require specific management strategies that prioritise safety and in doing so promote and ensure inclusivity for all.